Sistem Informasi Absensi Karyawan Berbasis Mobile dengan Fitur Geolocation dan Pengelolaan Data Pegawai Berbasis Website - Aksayeth, Muhammad Bara; Rukmana, Rika; fadillah, yazidh; Haryono, Wasis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Manual employee attendance recording is still commonly used in many companies, despite its known weaknesses such as delayed data processing, high potential for fraud, and lack of efficiency. This study aims to design and develop a mobile-based employee attendance information system with geolocation features, integrated with a web-based dashboard for employee data management. The system was developed using the Waterfall model through several stages: observation, interviews, literature review, design, implementation, and testing. The mobile application was built using Flutter to record attendance with GPS-based location verification and selfie capture, while the website was developed using PHP and MySQL to manage employee data and attendance reports. The results show that the system can accurately record attendance data, reduce fraud, and simplify real-time monitoring by administrators. This system offers an efficient and transparent digital solution for companies in managing employee attendance.